Analysis of Batam Trans Bus Performance Quality on Urban Transportation System Activities in Supporting Availability of Regional Facilities - Suhara, Yayat Yatna; Sidabutar, Yuanita FD; Suciati, Herlina; Panusunan, Panusunan (Borong Newinera Publisher, 2024)
Batam City is one of the developing citiesBus Rapid Transit (BRT) as a mode of mass transportation for the community. Bus Rapid Transit (BRT) operations began in 2004. The existence of the Trans Batam Bus is still less popular with the public because other modes of transportation are easier to use as daily public transportation. Apart from that, the use of private vehicles is still high in Batam City. Trans Batam buses are provided as an integrated mode of transportation to serve the community and provide comfortable, safe facilities and prioritize safety. This research aims to identify the performance of the Trans Batam Bus transportation system based on the SPM for Road-Based Mass Transport (Permen No. 27 of 2015). The research method uses a questionnaire as a research instrument with data processing using scoring (Likert Scale). Multiple linear regression analysis method to determine the magnitude of performance. The sample was 99 respondents who used Trans Batam services. The research results show that aspects that are considered good and efficient according to public perception are busway facilities (0.748), integration with other transportation systems (0.413), and punctuality (0.233). The results of statistical calculations show that there is an influence of public interest of 72.5% on the performance of Bus Rapid Transit (BRT) with the aspects that have the most significant influence, namely security and safety.